Clinical significance of telomerase and its associate genes expression in the maintenance of telomere length in squamous cell carcinoma of the esophagus - Hsu, Chung-Ping (World J Gastroenterol, 2005)
AIM: To observe the interaction between the expression of telomerase activity (TA) and its associate genes in regulation of the terminal restriction fragment length (TRFL) in esophageal squamous cell carcinoma (SCC). METHODS: Seventy-four specimens of esophageal SCC were examined. The TA was measured by telomeric repeat amplification protocol (TRAP) assay, and the associated genes [human telomerase-specific reverse transcriptase (hTERT), hTERC, TP1, c-Myc, TRF1, and TRF2] were detected using RT-PCR method. The TRFL was measured by Telomere Length Assay Kit and Southern blotting. The correlations between the expression of telomerase and its associated genes with the TRFL and survivals were examined. RESULTS: Expressions of the TA, hTERT, hTERC, TP1, c-Myc, TRF1, and TRF2 genes were observed in 85.1%, 64.9%, 79.7%, 100.0%, 94.6%, 82.4%, and 91.9% of the tumor tissues, respectively. The TRFL of the tumor and normal esophageal tissues were 2.70±1.42 and 4.93±1.74 kb, respectively (P<0.0001). The TRFL of the telomerase positive and telomerase negative tumor tissues were 2.72±1.44 and 2.58±1.32 kb, respectively (P = 0.767). The TRFL ratios (TRFLR) of the telomerase positive and telomerase negative tumor tissues were 0.55±0.22 and 0.59±0.41, respectively (P = 0.742). The expression rates of h-TERT (P = 0.0002), hTERC (P<0.0001), and TRF1 (P = 0.002) in the tumor tissues are higher than those of the normal paired tissues. Though TA is markedly activated in tumor tissues (P<0.0001), its expression is not related to clinicopathological parameters including gender, tumor differentiation, and TNM stages. The cumulative 4-year survival rates of telomerase positive and telomerase negative cases were 35.86% and 31.2%, respectively (P = 0.8442). The cumulative 4-year survival rates of patients with their TRFLR ≤85% and >85% were 38.7% and 15.7%, respectively (P = 0.1307). CONCLUSION: Though telomerase expression is not related to tumor stages and prognosis, our data support that the TA increased as the TRFL decreased, probably under the control of hTERT, hTERC, and TRF1. When telomerase expression was activated, only TRF2 overexpression persisted to stabilize T-loop formation. Furthermore, as the TRFLR decreased to 85%, a trend of better prognosis was observed. Cox model analysis indicates a higher t/n TRFLR and distant metastasis are independent poorer prognostic factors (P = 0.035 and P = 0.042, respectively).